ENERGY HARVESTER SYSTEM BY USING ANAEROBIC DIGESTION AND FOOD WASTE AS FUEL - SYED MOHD NAIM, SYED AHMAD NABIL (2017)
Increment of food waste has becoming a rising epidemic to the environment, economy and social in Malaysia. Food waste production leads to the increment of number and size of landfills in Malaysia. These landfills produce landfill gasses that consists of methane and carbon dioxide as its main constituents, and leachate that destroy the crops that the landfill resides. Ultimately, not only food waste generation leads to wasting precious land, but also the emission of carbon dioxide and methane leads to climate change. This paper proposes an alternative/solution to this problem. The proposed design is to act as a storage system for the food waste that is generated by the consumer. The proposed design serves the purpose of being a portable, low-cost, and easy to handle by the user for the use of converting the food waste to biogas and nutrient rich slurry. Anaerobic digestion is the process that is used to convert the food waste. The biogas produced by this process is odorless, colorless and combustible. The calorific value of biogas is similar to fossil fuels which can be used for energy conversion. In the proposed design, a network of sensors is installed to monitor and adjust the conditions of the environment of the storage system to optimize the conversion of food waste to biogas. The network of sensors consists of temperature, Ph and gas sensors. The data that is collected from the sensors are monitored by an Arduino Mega 2560 microcontroller. The data is then displayed onto an LCD display located on top of the system. The targeted audience for this system is for any average consumer for household use, or any commercial sites such as restaurants, hotels, factories, offices, etc. 6